Analisis Evaluasi Proses Pembelajaran Daring Melalui Aplikasi Whatsapp Kelas V SD Negeri Sukoagung - Arif Dias Artama; Filia Prima; Mei Fita Asri Untari (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2022)
Online Learning activities that done by each School Institution are option issued by the ministry of Education and culture of Republic Indonesia as action to prevent the spread of Covid-19 ended. Used whatsapp as media for Online learning is one of the way of teachers do the flexible learning and easy to reach by the students Elementary School. The implementation of online learning through whatsapp also need evaluation to know what the purpose itself and learning barriers that need so that learning runs effectively. The purpose this research is to describe the result of evaluation of online learning programs via whatsapp in class V Sukoagung Elementary School. This study uses a descriptive qualitative approach with data collection techniques through interview, observation, questionnaires and documentation. The observation results are the implementation of online learning in class V Sukoagung Elementary School has been going well and deserves to be used as a substitute for directly learning during an emergency. Competencies belonged by teachers using pedagogy,social and personality show that teachers are able to provide online learning well, but teachers still not fully have a master of technology in learning activities.